Easements relating to land surveying and title examination - Wilson, Donald A., 1941- (John Wiley & Sons, 2013)
Concise, in-depth coverage of the complex issues of easements and their reversion The definition, use, defense, and retirement of easements are areas of active work for land surveyors, lawyers, and the holders and buyers of easements, such as utility companies and highway departments. Easements Relating to Land Surveying and Title Examination is the most up-to-date reference that succinctly and incisively covers easements and reversions, written for land surveyors and title examiners. This comprehensive guide covers the various forms of easements, their creation, rever.